2017
DOI: 10.1186/s12887-017-0943-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic parameters of the liver, spleen and kidneys among a cohort of school children in Sri Lanka

Abstract: BackgroundLiver, spleen and kidney dimensions on ultrasonography vary with the age, weight and ethnicity. Reference standards of these parameters for normal Sri Lankan children are not available. Our aim was to establish normative data for longitudinal length of liver, spleen and kidneys in healthy children.MethodThree hundred fifty-seven children, 5–13 years of age were selected from two randomly selected schools in the Gampaha district in the western province of Sri Lanka. A questionnaire was administered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
1
17
1
2
Order By: Relevance
“…The results of our study are in accordance with the findings of those studies. On the other hand, in some studies weight or age correlate better with splenic length ( 3 , 13 , 19 22 ) .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of our study are in accordance with the findings of those studies. On the other hand, in some studies weight or age correlate better with splenic length ( 3 , 13 , 19 22 ) .…”
Section: Discussionmentioning
confidence: 94%
“…There are no significant differences between the sexes in children. Sex certainly is not a determining factor for organ dimensions in the pediatric age group ( 3 , 10 , 12 , 13 ) . We did not find any significant difference in spleen sizes between the two sexes of any age group (t-test, p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The correlations of the anthropometric body indices versus dimensions of several body organs have been documented in litearture [9, 10]. It is well known that renal size is related to age, height and weight of children.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 9 , 10 , 14 - 15 However, in a few other studies, the patient's weight showed the strongest correlation with splenic length. 16 , 19 …”
Section: Discussionmentioning
confidence: 99%